Beyond mistreatment: Learner neglect in the clinical teaching environment. (3rd August 2019) - Buery-Joyner, Samantha D.; Ryan, Michael S.; Santen, Sally A.; Borda, Allison; Webb, Timothy; Cheifetz, Craig
Abstract: Medical student mistreatment has been recognized as a deterrent to education as it interferes with the learning process and contributes to student burnout and attrition. Medical schools and leaders in undergraduate medical education have expended tremendous effort in addressing this phenomenon in hopes of eradicating mistreatment. However, there is a spectrum of behaviors that negatively impact the learning environment beyond that which is considered frank mistreatment. In this conceptual article, the authors propose the concept of learner neglect for the consideration by educators and researchers. This is a term for a range of behaviors exhibited intentionally or unintentionally by a supervisor that prevent a learner from reaching his or her potential. While the behaviors may overlap with mistreatment, they do not always fit within the definition of mistreatment. This concept is illustrated in the context of optimal and suboptimal teaching behaviors that commonly occur within the ecosystem of clinical education. Descriptions and examples are provided for both intentional and unintentional learner neglect. The authors hypothesize possible short- and long-term impacts of learner neglect, describe contributors to its prevalence, and offer questions for key stakeholders to consider in an effort to recognize, study, and ameliorate this issue within medical education programs.